CUT&Tag reveals unconventional G-quadruplex landscape in Mycobacterium tuberculosis in response to oxidative stress - Ilaria Maurizio; Emanuela Ruggiero; Irene Zanin; Marta Conflitti; Giulia Nicoletto; Roberta Provvedi; Sara N. Richter (Nature Communications)
Abstract Mycobacterium tuberculosis (Mtb), the causative agent of tuberculosis, remains a global health threat due to increasing drug resistance and high mortality rates. To combat tuberculosis effectively, novel therapeutic targets are urgently needed. G-quadruplexes (G4s) represent promising candidates for this purpose. In this study, we successfully apply the cleavage under targets and tagmentation (CUT&Tag) technique for the first time in bacteria, mapping the G4 landscape in Mtb under standard and oxidative stress conditions, the latter mimicking the environment Mtb faces within macrophages. We validate the CUT&Tag protocol using an antibody against the RNA polymerase β-subunit, confirming its association with actively transcribed genes. Employing the anti-G4 antibody BG4, we discovered that Mtb G4s, unlike their eukaryotic counterparts, predominantly locate within gene coding sequences and consist of two-guanine tract motifs. Notably, oxidative stress increases G4 formation, correlating with reduced gene expression. Our findings provide the first evidence of G4 formation in Mtb cells and suggest their potential role in bacterial survival within macrophages. This study demonstrates the successful application of CUT&Tag in bacteria and unveils an unconventional G4 landscape in Mtb, offering new insights into bacterial stress response mechanisms and potential therapeutic targets.